Radial flow behaviors of a rough Beishan granite fracture under normal and thermal loadings - Xingguang Zhao; Dongjue Fan; Zhihong Zhao; Liang Chen; Ju Wang (Underground Space)
During the operation of a deep geological repository in crystalline rocks for disposal of high-level radioactive waste, understanding the seepage behaviors of fractured crystalline rocks under coupled thermo-hydro-mechanical conditions is essential for the performance assessment of deep geological repositories. In this study, radial flow tests on cylindrical Beishan granite specimens with a single artificial fracture were conducted using the MTS 815 rock mechanics testing system to investigate the influence of normal stress and temperature on radial flow behaviors of rough rock fractures. Steady state method was used to measure fracture permeability, and an axial extensometer was used to measure fracture deformation during compression. A three-dimensional blue light scanner was used to characterize fracture surface morphology. Experimental results indicate that fracture permeability decreases nonlinearly with the increase of normal stress or temperature, and normal stress has a more significant influence on fracture permeability than temperature. The evolution of three-dimensional non-uniform distribution of voids under compression was numerically obtained, and the variogram was employed to quantify the non-uniform distribution characteristics of mechanical apertures. In addition, a radial flow model considering non-uniform distribution of apertures is proposed to predict the normal stress- and temperature-dependent seepage behaviors of rock fractures, and the predictions were found to be in good agreement with experimental data.